Millennials, Technology, and English Language Teaching - Nurul An-Nisa; Giarni Alfi Astika; Tono Suwartono (Tarling : Journal of Language Education, 2021)
At present, the development of technology has increasingly advanced. This situation requires millennial to apply technology in every area of ​​life. It makes millennial generation very dependent on technology. Technology plays an important role in education context especially in English language teaching. The presence of technology makes teachers and students easier to get learning material and develop learning instructions. They can use any media technology to support the success of teaching and learning activities. There are various media applications that can be used to help the English teaching process both in the classroom and outside the classroom. In the use of electronic media applications in the learning process called e-learning. Teachers must be able to choose activities that are creative and innovative. It can make teaching activity more interesting and not get bored. This article discusses about the relationship among millennial, technology, and English language teaching to create great teachers in the future.